Computer usage and task-switching during resident’s working day: Disruptive or not? - Méan, Marie; Garnier, Antoine; Wenger, Nathalie; Castioni, Julien; Waeber, Gérard; Marques-Vidal, Pedro (PLOS ONE, 2017)
Background Recent implementation of electronic health records (EHR) has dramatically changed medical ward organization. While residents in general internal medicine use EHR systems half of their working time, whether computer usage impacts residents’ workflow remains uncertain. We aimed to observe the frequency of task-switches occurring during resident’s work and to assess whether computer usage was associated with task-switching. Methods In a large Swiss academic university hospital, we conducted, between May 26 and July 24, 2015 a time-motion study to assess how residents in general internal medicine organize their working day. Results We observed 49 day and 17 evening shifts of 36 residents, amounting to 697 working hours. During day shifts, residents spent 5.4 hours using a computer (mean total working time: 11.6 hours per day). On average, residents switched 15 times per hour from a task to another. Task-switching peaked between 8:00–9:00 and 16:00–17:00. Task-switching was not associated with resident’s characteristics and no association was found between task-switching and extra hours (Spearman r = 0.220, p = 0.137 for day and r = 0.483, p = 0.058 for evening shifts). Computer usage occurred more frequently at the beginning or ends of day shifts and was associated with decreased overall task-switching. Conclusion Task-switching occurs very frequently during resident’s working day. Despite the fact that residents used a computer half of their working time, computer usage was associated with decreased task-switching. Whether frequent task-switches and computer usage impact the quality of patient care and resident’s work must be evaluated in further studies.